KOMPETENSI KEPALA DESA DALAM PENYELENGGARAAN PEMERINTAHAN DI DESA TOUNELET KECAMATAN KAKAS KABUPATEN MINAHASA - KUENGO, SYAHRUL; Posumah, Johnny Hanny; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: The implementation of village governance requires more optimal handling on the aspect of RuralApparatus Human Resources, in improving the competence of village head and village apparatus. In termsof management, it is necessary to increase the capacity of village government in village developmentplanning and budgeting, village financial management, village head leadership, village policy formulation,and village services. Based on the problems presented, this study aims to determine the competence of theVillage Head in the administration in the Village Tounelet Kakas District Minahasa District This researchuses qualitative method, which is a contextual research that makes man as an instrument, and adapted to areasonable situation in relation to data collection which is generally qualitative. The result of the researchshows that the competence of Tounelet Village Head in the administration of village government is seenfrom the competence of knowledge and attitude competence is good enough / adequate; But seen from thecompetence of skills and skills are still inadequate.Keywords: Village Head Competency, Government Implementation